CT and MRI of Aortic Coarctation: Pre- and Postsurgical Findings - Karaosmanoglu, Ali Devrim; Khawaja, Ranish Deedar Ali; Onur, Mehmet Ruhi; Kalra, Mannudeep K. (Amer Roentgen Ray Soc, 2015)
OBJECTIVE. The purpose of this article is to summarize the roles of CT and MRI in the diagnosis and follow-up of patients with aortic coarctation. CONCLUSION. Aortic coarctation is a common congenital heart disease accounting for approximately 6-8% of congenital heart defects. Despite its deceptively simple anatomic presentation, it is a complex medical problem with several associated anatomic and physiologic abnormalities. CT and MRI may provide very accurate information of the coarctation anatomy and other associated cardiac abnormalities.
Keywords: aortic coarctation; congenital heart disease; CT; MRI